T cells isolated from patients with checkpoint inhibitor-resistant melanoma are functional and can mediate tumor regression. (24th April 2018) - Andersen, R; Borch, T H; Draghi, A; Gokuldass, A; Rana, M A H; Pedersen, M; Nielsen, M; Kongsted, P; Kjeldsen, J W; Westergaard, M C W; Radic, H D; Chamberlain, C A; et al.
Abstract: Background: Almost half of the patients with metastatic melanoma obtain only short-term or no benefit at all from checkpoint inhibitor (CPI) immunotherapy. In this study, we investigated whether the immune system of patients progressing following CPI treatment was able to generate functional tumor-specific immune responses. Materials and methods: Tumor-infiltrating lymphocytes (TILs) were isolated and expanded from metastatic melanoma lesions which progressed during or after anti-programmed cell death protein 1 (PD)-1 and anti-Cytotoxic T-Lymphocyte Antigen 4 (CTLA-4) treatment. Tumor-specific immune responses were assessed with co-culture assays of TILs and autologous tumor cells. Results: TILs from 23 metastases of individual patients could be assessed for T cells recognition of autologous tumor cells. All metastases were progressive on or following anti-PD-1 (23/23, 100%), and the majority also after anti-CTLA-4 (17/23, 74%). Functional antitumor immune responses were detected in 19/23 patients (83%). Both CD8 + (in 18/23 patients, 78%) and CD4 + (in 16/23 patients, 70%) TILs were able to recognize autologous tumors. A large fraction of CD8 + TILs (median 23%, range 1.0%–84%) recognized tumor cells. This is similar to the cohorts of unselected patient populations with metastatic melanoma presented in previous studies. The localization of intratumoral immune infiltrates was heterogeneous among samples. In a phase I/II clinical trial, TILs were administered with lymphodepleting chemotherapy, pegIFNα2b and interleukin-2 to 12 patients with CPI-resistant melanoma. Out of 12 patients who previously failed CPI therapy, treatment with TILs resulted in two partial responses, of which one is ongoing. Conclusions: Tumor-reactive T cells appear to heavily infiltrate the tumor microenvironment of patients who failed previous CPI treatment. These patients can still respond to an infusion of unselected autologous TILs. Our results warrant further testing of novel immune re-activation strategies in melanoma patients who failed multiple CPI therapy.